2018
DOI: 10.1007/s10681-018-2125-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs for resistance to Fusarium wilt and Ascochyta blight in a recombinant inbred population of chickpea (Cicer arietinum L.)

Abstract: Fusarium wilt (FW; caused by Fusarium oxysporum f. sp. ciceris) and Ascochyta blight (AB; caused by Ascochyta rabiei) are two major biotic stresses that cause significant yield losses in chickpea (Cicer arietinum L.). In order to identify the genomic regions responsible for resistance to FW and AB, 188 recombinant inbred lines derived from a cross JG 62 9 ICCV 05530 were phenotyped for reaction to FW and AB under both controlled environment and field conditions. Significant variation in response to FW and AB w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…They further mapped the major QTLs (QTL-1 and QTL-2) in linkage group 6 and 1[ 30 ]. There are several other studies indicating that the loci governing the disease resistance are quantitative in nature [ 32 36 ]. A study showed that the inheritance is genotype specific [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They further mapped the major QTLs (QTL-1 and QTL-2) in linkage group 6 and 1[ 30 ]. There are several other studies indicating that the loci governing the disease resistance are quantitative in nature [ 32 36 ]. A study showed that the inheritance is genotype specific [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resistant check used was PB 5. These are commonly used chickpea varieties used as checks for ascochyta screening [ 22 , 23 ]. Sowing was done on appropriate time in each winter season using recommended agronomic practices.…”
Section: Methodsmentioning
confidence: 99%
“…However, Jingade and Ravikumar (2015) reported one major QTL GSSR 18-TC14801 on LG 1 for Foc1 resistance, which explained up to 71% phenotypic variation (PV). Subsequently, a major QTL FW-Q-APR-2-1 on CaLG02 and two other minor QTLs FW-Q-APR-4-1 and FW-Q-APR-6-1 on CaLG4 and CaLG6, respectively were identified for resistance against Foc1 and Foc3 (Garg et al, 2018). Considering Foc5, monogenic/oligogenic nature has been established for resistance loci on LG 2 (Tekeoglu et al, 2000;Winter et al, 2000;Castro et al, 2010).…”
Section: Identification Of Resistance Loci and Molecular Marker For Fmentioning
confidence: 99%
“…QTLs for resistance to FW were reported earlier mainly on CaLG02 and CaLG04 (Cobos et al 2009 ; Gowda et al 2009 ). Nevertheless, novel QTLs were also mapped on CaLG05 and CaLG06 (Sabbavarapu et al 2013 ; Garg et al 2018 ). Previous efforts in identifying different FW-resistant genes (Sharma et al 2005 ), race-specific unique and rare alleles (Sharma et al 2014 ), tagging of molecular markers linked to resistance (Sharma and Muehlbauer 2005 ) can accelerate the development of improved cultivars in chickpea through MABC.…”
Section: Discussionmentioning
confidence: 99%